2017
DOI: 10.5380/ce.v22i3.50609
|View full text |Cite
|
Sign up to set email alerts
|

Perfil Epidemiológico E Seguimento Após Alta De Pacientes Internados Em Unidade De Terapia Intensiva

Abstract: RESUMO: Descrever o perfil epidemiológico e o seguimento após alta de pacientes internados em uma unidade de terapia intensiva. Pesquisa descritiva, seccional e de abordagem quantitativa, por meio de análise documental dos prontuários eletrônicos de pacientes adultos, internados na unidade de terapia intensiva em um hospital de atenção terciária na cidade do Rio de Janeiro, no período de novembro de 2014 a novembro de 2015. Na amostra (n=573) 73% apresentaram idade igual ou acima de 60 anos, que foi associada … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 17 publications
0
8
0
5
Order By: Relevance
“…e adjusted model described the association between older age and prevalence of mortality. Other studies identified similar relationship in ICU patients; however, the risk of death was linked to elderly patients [1,2,23,25,27]. Incidence of chronic diseases among younger adults has been observed in Brazil.…”
Section: Discussionmentioning
confidence: 69%
See 4 more Smart Citations
“…e adjusted model described the association between older age and prevalence of mortality. Other studies identified similar relationship in ICU patients; however, the risk of death was linked to elderly patients [1,2,23,25,27]. Incidence of chronic diseases among younger adults has been observed in Brazil.…”
Section: Discussionmentioning
confidence: 69%
“…This study identified a 21% ICU mortality rate among patients in the hospital of Sergipe, northeastern Brazil. The mortality rate is considered high when compared to other national and international studies [ 1 , 2 , 23 25 ]. Age, admission from inpatient unit, sepsis, hydroelectrolyte imbalance, changes in glycemic index, tube feeding, mechanic ventilation, sedation with fentanyl, insulin use, and higher Charlson scores were associated with mortality in this study.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations